Improving corporate profitability from the inside out with environmental performance: an empirical analysis based on Chinese listed company data - Hu, Jing; Zhao, Yanyun (Frontiers in Environmental Science, 2024)
This study uses data from listed companies in China from 2008 to 2021, constructs a comprehensive evaluation of corporate environmental performance from the perspective of internal efficiency and externalities based on the text analysis method, and analyzes the impact and mechanism of environmental performance on profitability. In addition, we find that improving environmental performance can significantly increase profitability, especially if the company tackles pollution at the source. Furthermore, the impact of environmental performance on profitability tends to be driven by external markets. Obtaining environmental certifications, awards, and green patents can provide positive feedback and significantly increase profitability. In addition, the mechanism analysis shows that environmental performance affects firm profitability by improving green technology innovation, reducing financing constraints and increasing operating income. Finally, the results of the heterogeneity analysis show that the profitability-enhancing effect of environmental performance is stronger in non-state-owned firms, in clean industries firms and in regions with carbon emission trading.